2017
DOI: 10.1083/jcb.201702022
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-driven assembly of a cortical anchor for mitochondria and dynein

Abstract: Kraft and Lackner demonstrate that mitochondria drive the assembly of a tether, which serves to stably anchor the organelle itself as well as dynein to the plasma membrane. Thus, mitochondria–plasma membrane tethering influences when and where dynein is anchored, adding to the growing list of interorganelle contact site functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
84
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(97 citation statements)
references
References 56 publications
(110 reference statements)
11
84
0
Order By: Relevance
“…In the vast majority of cells expressing wildtype Num1, the number of mitochondria-associated clusters was equivalent to the total number of clusters per cell (Figure 2(c)), consistent with mitochondria-dependent cluster assembly [17]. In contrast, in all cells expressing PAN, the number of mitochondria-associated clusters was far lower than the total number of clusters per cell (Figure 2(c)).…”
Section: Resultssupporting
confidence: 57%
See 4 more Smart Citations
“…In the vast majority of cells expressing wildtype Num1, the number of mitochondria-associated clusters was equivalent to the total number of clusters per cell (Figure 2(c)), consistent with mitochondria-dependent cluster assembly [17]. In contrast, in all cells expressing PAN, the number of mitochondria-associated clusters was far lower than the total number of clusters per cell (Figure 2(c)).…”
Section: Resultssupporting
confidence: 57%
“…Importantly, we found that mitochondria were also present at the vast majority of sites where cortical dynein foci and PAN clusters colocalized (Figure 4(a and b)). The percent of cortical dynein foci that colocalized with both PAN clusters and mitochondria (~ 84%) was strikingly similar to the percent of cortical dynein foci that colocalized with both wildtype Num1 clusters and mitochondria (~ 86%; Figure 4(a and b)) [17]. This was particularly notable given the fact that only ~ 21% of PAN clusters are mitochondria-associated, while ~ 95% of wildtype Num1 clusters are mitochondria-associated (Figure 2(d)).…”
Section: Resultsmentioning
confidence: 72%
See 3 more Smart Citations